Generosity From The Quranic Perspective: Inspiration For Philanthropy-Based Start Ups - Mawar Ardiansyah; Taufik Warman Mahfuzh; Syamhudian Noor (STAI Kuala Kapuas, 2025)
This study aims to explore generosity from the perspective of the Qur'an as an inspiration for the development of philanthropic start-ups. By integrating Islamic philanthropic values, this study seeks to demonstrate the relevance of the teachings of the Qur'an in creating a business model that not only prioritizes financial profit, but also social welfare. The method used is qualitative descriptive research with literature analysis. Data were collected from secondary sources, including books and academic articles, as well as related publications that explore the verses of the Qur'an on generosity. The findings of the study indicate that the principles contained in verses such as Surah Al-Imran 3:92 and Surah Al-Baqarah 2:261-262 underline the importance of goodwill, social responsibility, and wealth sharing to create a positive impact. Philanthropic start-ups, inspired by these teachings, can distribute profits to those in need and make social contributions an integral part of their business model. Thus, this study concludes that the implementation of the values ​​of generosity in the Qur'an can contribute significantly to the creation of better social and economic justice in Indonesia..